Influence of Dose of Organic and Nonorganic Fertilizers to Yield of Rice (Oriza sativa L.) and Soil Chemical Compound on Inceptisol Kerambitan Tabanan - I GEDE PADMANABHA; I DEWA MADE ARTHAGAMA; I NYOMAN DIBIA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology))
ABSTRACT Influence of Dose of Organic and Nonorganic Fertilizers to Yield of Rice (Oriza sativa L.) and Soil Chemical Compound on Inceptisol Kerambitan Tabanan A factorial experiment was conducted to study the effect of organic and inorganic fertilizer rates on rice yield and soil chemical characteristics under Inceptisol soil condition, located in subak Serongga, village of south Selingsing, Kerambitan district, Tabanan regency. Prior and after the experiments, soil analysis was conducted at the Soil Laboratory, Faculty of Agriculture, Udayana University. A Randomized Block Design (RBD) trial was set up, which consisted of two factors: the organic (manure) rates (K) and the inorganic fertilizer rates (P). Plant parameters observed including maximum plant height, maximum number of tillers, number of productive tillers, dry weight of grain after harvesting and oven grain dry weight. In addition, soil chemical properties were also analyzed which covering N-total, available P, available K, and C-organic. The result of statistical analysis showed that the interaction between organic and inorganic fertilizers were significantly different (P<0,05) on the maximum height of plant, while the other variables did not show any differences (P>0,05).   Key words: organic and nonorganic fertilizer, rice, soil chemical compound